Technical and vocational education and training in Tajikistan and other countries in Central Asia key findings and policy options - Izawa, Eiko Kanzaki (Asian Development Bank, 2021)
Cover -- Title -- Copyright -- Contents -- Tables, Figures, and Boxes -- Acknowledgments -- Abbreviations -- Executive Summary -- I. Introduction -- A. Independence of Central Asian Countries -- B. Geographic and Demographic Features of Central Asian Countries -- II. Macroeconomics and Labor Market in Central Asia -- A. Tajikistan -- B. Other Central Asian Countries -- III. Technical and Vocational Education and Training History, Policies, Systems, and Performance -- A. Technical and Vocational Education and Training Policies and Systems in the Former Soviet Union -- B. TajikistanC. Other Central Asian Countries -- IV. ADB in Central Asia -- A. Tajikistan -- B. Kyrgyz Republic -- C. Uzbekistan -- V. Many Challenges Remain -- A. Technical and Vocational Education and Training Governance and Management -- B. Responsiveness of Technical and Vocational Education and Training System -- C. Quality and Relevance of Technical and Vocational Education and Training -- D. Shortage of Jobs -- E. School-to-Work Transition -- F. Distance Education and E-learning -- G. Regional Coordination and CollaborationVI. Recommendations for Future Technical and Vocational Education and Training Engagements -- A. Increasing the Technical and Vocational Education and Training System's Responsiveness -- B. Quality and Efficiency of Technical and Vocational Education and Training -- C. Public-Private Partnerships and Industry Partnerships -- D. Easing School-to-Work Transition -- E. Gender Equality -- F. Information and Communication Technology and Digital Skills -- G. Strengthened Regional Cooperation -- References